Home Care of Patients with Head Injury: Are We Neglecting the Caregivers? - Shoaib, Yawar; Dagar, Amit; Reyaz, Abraq Asma (Indian Journal of Neurotrauma, 2017)
In the absence of professional long-term care facilities in India, home care to patients with head injury is usually provided by family members. In this scenario, the mental health of the caregivers remains an important issue. This factor is constantly neglected by the health care providers and the society alike. With the result, the caregivers are prone to depression, anxiety, and other forms of mental illnesses. This also has a negative impact on the recovery and rehabilitation of the head injury survivor. In this article, the authors have reviewed relevant literature to find out the extent and prevalence of this problem among home caregivers of patients with head injury. The authors have also highlighted the possible measures that the treating neurosurgeon and the society can take for effective management of these issues. Their aim is to make the neurosurgeon and other health care providers aware of this issue and its various ramifications.
Keywords: caregiver; depression; anxiety; head injury